Assessment of Readability of Vietnamese Text - Hien Pham; Huyen Nguyen Thi Minh; Phuong Le-Hong (Scholars, 2025)
This paper presents a study that has systematically considered the impact of linguistic features on readability for Vietnamese texts. We used a set of selected texts from the primary school, junior high school and high school Vietnamese textbooks as our input data set. The set of linguistic features accounted for various aspects, such as morphological features, part-of-speech features, syntactic features and discourse features. Our study targets qualitatively and quantitatively developing a readability scale for readers who wish to measure their texts to the intended readers. The applications and implications of the resulting outcomes from this study can benefit textbook composers, who are working on the new set of K-12 textbooks, such as students, teachers, and publishers.